If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -5 = 3x + 23 Reorder the terms: -5 + 7y = 3x + 23 Reorder the terms: -5 + 7y = 23 + 3x Solving -5 + 7y = 23 + 3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 7y = 23 + 5 + 3x Combine like terms: -5 + 5 = 0 0 + 7y = 23 + 5 + 3x 7y = 23 + 5 + 3x Combine like terms: 23 + 5 = 28 7y = 28 + 3x Divide each side by '7'. y = 4 + 0.4285714286x Simplifying y = 4 + 0.4285714286x
| 4(x+1)-3(x-3)=25 | | -7x+3x^2+2=0 | | (x+4)2=81 | | 137=x+y | | 10x+12=112 | | -3x^2-2x+4=0 | | 4x+62=9x-13 | | 30-6x=3x+18 | | 10-6x=3x+18 | | =4x+15 | | -35-3x=9x+19 | | 130=2x-y | | -2(x+9)+91=13+24 | | 2(111)=d | | 7x+26=4x+77 | | 4x-6x=7 | | 34-2x=7x+21 | | -3x^2-4x+1=0 | | 3-8s=-29 | | 4x+y+x+3y=180 | | x^2-6x+9=2 | | 66x+35=25 | | (7-8)+17= | | 10x-28=4x+22 | | x^2=x+4 | | 97x+66=10 | | p(x)=-2x^2+60x-25 | | 169-2x=25x+22 | | 86x-53=9 | | 90-2x=4x+24 | | 4x^2+48x+27=0 | | y+9y+5=15 |